Experimental warming decouples plant–fungal symbiont interactions and leads to a more conservative ecosystem - Lara Souza; Aimée T. Classen; Jennifer A. Rudgers; Cassandra M. L. Miller; Jessica A. M. Pyle; Ruth Simberloff; James A. Fordyce; John Harte; Stephanie N. Kivlin (Proceedings of the National Academy of Sciences, 2026)
Climate forecasts project rising temperatures for every land surface on Earth. Predicting the consequences of climate warming poses a challenge for science and society. Shifts in plant–microbial interactions can lead to significant changes in ecosystem-level functioning. In one of the world’s longest climate change experiments, we studied the effects of 29 y of warming on a native subalpine grassland in the Rocky Mountains of North America. Warming caused a transition from herbaceous to woody-dominated vegetation, with shrubs increasing by 150% in warmed plots and a concurrent ~28% decrease in both forbs and grasses. This shift was accompanied by functional traits changing by 20% toward more conservative values relative to acquisitive ones. Consequently, plant–symbiont associations decreased with root-associated fungi—arbuscular mycorrhizal fungal and septate root colonization—both declining by 17 to 20% under warming. In turn, soil saprotrophic fungi increased by 10% with warming. Strikingly, warming decoupled above- and belowground communities and their functions. This decoupling was evident as plant–available phosphorus increased and both individual plants and plant communities reduced their reliance on mycorrhizal fungi, while plant connectedness to decomposer fungi tightened. Our results suggest that, as the planet warms, subalpine grasslands will become more conservative and desert shrubland-like in both above- and belowground properties.